Dynamic Performance Characteristics of Floating-Ring Bearings With Varied Oil-Injection Swirl-Control Angles - Tamunodukobipi, Daniel; Kim, Chang Ho; Lee, Yong-Bok (ASME, 2015)
Hydrodynamic instability is a prime causative of performance irregularities and violent vibrations in floating-ring bearing (FRB) supported turbosystems. The quest for energy-efficient solutions to this has stimulated the development of diverse FRB design-geometries, dimensional relationships, and surface-contours. Unfortunately, these modifications are characterized mainly by model-predictors, which results lack sufficient test-data to benchmark their authenticities. This work presents the concept and the test-data of flow redirection in FRBs by using an oil-injection swirl-control mechanism (OISCM) to attenuate rotordynamic instabilities. FRBs with radius ratio = 1.75 and clearance ratio -1.5 are tested for various OISCM angles (0 deg, 30 deg, and 60 deg) and under a specific load =50 kN/m(2). The test results indicate that FRBs with OISCM demonstrate substantial improvements in damping and stability characteristics. Their whirl-frequency-ratio (WFR) and cross-coupled forces are lower because of improved symmetry of films' pressure-forces (K-xx approximate to K-yy). Although the magnitudes of direct damping are higher (|C-xx| = 16.92 kN s/m for 60 deg and 6.03 kN s/m for 0 deg), the load capacity (K-xx) is slightly lower than the normal (0 deg), injection. Nonetheless, this discrepancy in load capacities becomes insignificant for speeds above 22 krpm. The WFR and subsynchronous amplitudes, which are graphic reflections of the bearing-based instability, become progressively smaller with increasing OISCM angle. However, this advantage at elevated speeds can only be sustained by a corresponding increase in oil-supply pressure to circumvent the advent of a starved inner-film and its attendant imbalance response and thermal growth. In closure, the OISCM bearing is more effective for mitigating rotordynamic instabilities in turborotors than conventional FRBs.